Evaluation of Chemical Health and Safety Management Using Task Risk Assessment in an Academic Chemical Process Laboratory - Wichitra Wongpromrat; Ermieza Sinin; Denise Ester Santiago-Sanchez (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the implementation of a chemical health and safety management system in an academic chemical process laboratory by identifying chemical and process-related hazards, assessing task-related risks, and examining the adequacy of existing safety control measures in preventing chemical exposure and health risks. Methodology: This study used a descriptive observational design. Tools included a structured laboratory safety checklist and a Task Risk Assessment matrix. Methods involved direct observation, document review, and semi-structured interviews. Reference standards included occupational safety and chemical health management principles. Data were analyzed qualitatively using risk categorization without specialized software. Main Findings: Laboratory activities involved chemical, mechanical, thermal, electrical, and housekeeping hazards. Task Risk Assessment results indicated low, medium, and high-risk tasks, with high-risk activities predominantly associated with chemical exposure during handling and storage, as well as process-related hazards involving heated, pressurized, or moving equipment. Although engineering, administrative, and personal protective equipment controls were available, their implementation was inconsistent and not always aligned with the identified chemical health risks. Overall, the implementation of chemical health and safety management was partially aligned with recognized safety management principles. Novelty/Originality of this study: This study provides task-level empirical evidence on chemical health and safety management in an academic chemical process laboratory and contributes to chemical health risk prevention by demonstrating how Task Risk Assessment can be applied to identify, prioritize, and control chemical exposure and process-related hazards in higher education laboratory environments.